2022
DOI: 10.1002/adom.202102757
|View full text |Cite
|
Sign up to set email alerts
|

Stationary, Continuous, and Sequential Surface‐Enhanced Raman Scattering Sensing Based on the Nanoscale and Microscale Polymer‐Metal Composite Sensor Particles through Microfluidics: A Review

Abstract: Surface‐enhanced Raman scattering (SERS) is a label‐free and accurate analytical technique for the detection of a broad range of various analytes such as, biomolecules, pesticides, petrochemicals, as well as, cellular and other biological systems. A key component for the SERS analysis is the substrate which is required to be equipped with plasmonic features of metal nanostructures that directly interact with light and targeted analytes. Either metal nanoparticles can be deposited on the solid support (glass or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 149 publications
(314 reference statements)
0
7
0
Order By: Relevance
“…Metal Microparticles: Due to the size and shape dependent properties, [112] metal microparticles play an extremely important role in metallic materials. As a result of a high ratio of surface area to volume, metal particles, especially in nanoscale, can be se-lected as effective catalysts for certain reactions.…”
Section: Spherical Functional Microparticlesmentioning
confidence: 99%
“…Metal Microparticles: Due to the size and shape dependent properties, [112] metal microparticles play an extremely important role in metallic materials. As a result of a high ratio of surface area to volume, metal particles, especially in nanoscale, can be se-lected as effective catalysts for certain reactions.…”
Section: Spherical Functional Microparticlesmentioning
confidence: 99%
“…The SERS has offered fascinating opportunities for a wide range of applications such as optoelectronics, photocatalysis, gas sensors, energy harvesting, etc. [ 4 , 5 , 6 ]. Regarding SERS enhancement mechanisms, the electromagnetic mechanism (EM) has been widely adapted as a dominant mechanism for various configurations of metallic micro- and nano-structures [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 , 5 , 6 ]. Regarding SERS enhancement mechanisms, the electromagnetic mechanism (EM) has been widely adapted as a dominant mechanism for various configurations of metallic micro- and nano-structures [ 5 , 6 , 7 , 8 ]. The EM is induced by the photon-driven excitation of localized surface plasmon resonance (LSPR), enabling giant enhancement of local e-fields that are significantly stronger than the incident photon [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, it is worth mentioning that the development and application of SERS technology depend on the design of the substrates as well as the construction of the corresponding module. [17][18][19][20][21][22] For many more substrates, especially practical SERS substrates, their current development needs to consider the characteristics of high reliability, fast operation, easy maintenance and portability. [23][24][25] Researchers found that binary nano-or micro-particles composed of a superparamagnetic core and Au or Ag nanoshell, such as Fe 3 O 4 microparticles coated with Au nanorods (Fe 3 O 4 @-AuNRs), 26 Fe 3 O 4 coated with Au nanoparticles (Fe 3 O 4 @-AuNPs), 27 etc., have a lot of advantages.…”
Section: Introductionmentioning
confidence: 99%